Therapist‐youth agreement on alliance change predicts long‐term outcome in CBT for anxiety disorders. (9th December 2015) - Fjermestad, Krister W.; Lerner, Matthew D.; McLeod, Bryce D.; Wergeland, Gro Janne H.; Heiervang, Einar R.; Silverman, Wendy K.; Öst, Lars‐Göran; De Los Reyes, Andres; Havik, Odd E.; Haugland, Bente S.M.
Abstract : Background: In individual cognitive behavioral therapy (ICBT) for youth anxiety disorders, it is unclear whether, and from whose perspective, the alliance predicts outcome. We examined whether youth‐ and therapist‐rated alliance, including level of youth‐therapist alliance agreement, predicted outcome in a randomized controlled trial. Methods: Youth ( N  = 91, M age = 11.4 years ( SD  = 2.1), 49.5% boys, 86.8% Caucasian) diagnosed with separation anxiety disorder, social phobia, or generalized anxiety disorder drawn from the ICBT condition of an effectiveness trial were treated with an ICBT program. Youth‐ and therapist‐rated alliance ratings, assessed with the Therapeutic Alliance Scale for Children (TASC‐C/T), were collected following session 3 (early) and 7 (late). Early alliance, change in alliance from early to late, and level of youth‐therapist agreement on early alliance and alliance change were examined, in relation to outcomes collected at posttreatment and 1‐year follow‐up. Outcome was defined as primary diagnosis loss and reduction in clinicians' severity ratings (CSR; Anxiety Disorders Interview Schedule; ADIS‐C/P) based on youth‐ and parent‐report at posttreatment and follow‐up, and youth treatment satisfaction collected at posttreatment (Client Satisfaction Scale; CSS). Results: Early TASC‐C scores positively predicted treatment satisfaction at posttreatment. Higher levels of agreement on change in TASC‐C and TASC‐T scores early to late in treatment predicted diagnosis loss and CSR reduction at follow‐up. Conclusions: Only the level of agreement in alliance change predicted follow‐up outcomes in ICBT for youth anxiety disorders. The findings support further examination of the role that youth‐therapist alliance discrepancies may play in promoting positive outcomes in ICBT for youth anxiety disorders. Clinical trial number NCT00586586, clinicaltrials.gov .